Customer Participation in Service Production and Delivery System - Sridhar, M. S. (Journal of Information and Knowledge, 1998)
Highlights significance of designing service delivery system, explains the integral role of customer in service production process, stresses the importance of customer-organisation interface, lists important ingredients of service package to be considered while designing customer interface, enumerates various dimensions of customer interface which can be positively made use of in design of service production and delivery system, discusses various ways and means of inducing and enhancing customer participation in service production and delivery system, emphasises the primacy of customer satisfaction in the evaluation of service organisation and finally concludes by pointing out the lopsided emphasis of librarianship on people-equipment dimension of customer-interface that too in terms of application software only.